2011
DOI: 10.47894/mpal.57.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Early Danian lacustrine - brackish water Ostracoda from the Deccan Inter-trappean beds near Jhilmili, Chhindwara District, Madhya Pradesh, India

Abstract: Twenty lacustrine – brackish water ostracode species are described from the recently discovered early Danian Planktic Foraminiferal Zone P1a sediments in the Deccan Inter-trappean beds of Jhilmili, ChhindwaraDistrict, Madhya Pradesh, India. These include two brackish water species – Neocyprideis raoi (Jain 1978), Buntonia sp. - and 18 lacustrine species of which one species - Strandesia jhilmiliensis - is new, 15 species are assigned to previously known species, and 2 species are left in open nomenclature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…So far, this species has been reported from various intertrappean sites in Gitti Khadan (Bhatia & Rana, 1984); Chandarki and Yanagundi, Gulbarga District (Whatley et al, 2002a); Mamoni (Whatley et al, 2003a); Mohgaon-Haveli and Takli (Khosla & Nagori, 2007; Khosla et al, 2007); Jhilmili (Khosla et al, 2009a, 2011a); Khar (Rathore et al, 2017); Manawar (Kapur et al, 2019) and recently reported from Gujri (Kshetrimayum et al, 2021). It is also described from the infratrappean bed (Lameta Group) of Dongargaon (Khosla et al, 2005) and Pisdura hill section (Khosla et al, 2011b).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, this species has been reported from various intertrappean sites in Gitti Khadan (Bhatia & Rana, 1984); Chandarki and Yanagundi, Gulbarga District (Whatley et al, 2002a); Mamoni (Whatley et al, 2003a); Mohgaon-Haveli and Takli (Khosla & Nagori, 2007; Khosla et al, 2007); Jhilmili (Khosla et al, 2009a, 2011a); Khar (Rathore et al, 2017); Manawar (Kapur et al, 2019) and recently reported from Gujri (Kshetrimayum et al, 2021). It is also described from the infratrappean bed (Lameta Group) of Dongargaon (Khosla et al, 2005) and Pisdura hill section (Khosla et al, 2011b).…”
Section: Methodsmentioning
confidence: 99%
“…The species name was retained as L. deccanensis (Khosla et al, 2005; Khosla et al, 2007) for the last name L. Bhatiai . The species has been described from the intertrappean bed of Mohagaon-Haveli and Jhilmili, Chhindwara District (Khosla & Nagori, 2007; Sharma & Khosla, 2009); Takli, Nagpur (Khosla et al, 2007); and the Lameta formation of Pisdura hill station, Nand-Dongargaon basin (Khosla et al, 2010, 2011b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations